2012
DOI: 10.1001/archpediatrics.2011.755
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Schoolwide Positive Behavioral Interventions and Supports on Bullying and Peer Rejection

Abstract: To build on prior research documenting the impact of School-wide Positive Behavioral Interventions and Supports (SWPBIS) on school climate and discipline problems to examine the extent to which it affects bullying and peer rejection during the transition into early adolescence. Design: Three-level models were fit using hierarchical linear modeling to determine the effect of SWPBIS on children's involvement in bullying. Setting: Thirty-seven Maryland public elementary schools. Participants: Data involved 12 344… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
123
1
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(137 citation statements)
references
References 46 publications
1
123
1
12
Order By: Relevance
“…Com relação ao objetivo dos estudos identificados nesta revisão, pode-se observar que a maioria (16) deles visava à diminuição dos índices de bullying no contexto escolar (Bauer, Lozano & Rivara, 2007;Bowllan, 2011;Caballo et al, 2011;Cross et al, 2011;Fung, 2011;Jenson, Dieterich, Brisson, Bender, & Powell, 2010;Joronen et al, 2012;Kärnä et al, 2011a;Kärnä et al, 2011b;Kim, 2006;McWilliam, 2010;Perkins, Craig, & Perkins, 2011;Salmivalli, Kärnä, & Poskiparta, 2011;Waasdorp, Bradshaw, & Leaf, 2012;Williford et al, 2012). Seis estudos tiveram ainda como objetivo testar intervenções que buscavam desenvolver alguma habilidade específica para o manejo do bullying, como, por exemplo, habilidades sociais, comportamentos antibullying, artes marciais, entre outros (Bauer et al, 2007;Cross et al, 2011;Domino, 2013;Fung, 2011;Kärnä et al, 2011a;McWilliam, 2010), sendo que alguns deles (6) também pretendiam que a intervenção interferisse em aspectos da saúde mental na infância (Domino, 2013;Fung, 2011;Kärnä et al, 2011b;Joronen et al, 2012;Tsang et al, 2011).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Com relação ao objetivo dos estudos identificados nesta revisão, pode-se observar que a maioria (16) deles visava à diminuição dos índices de bullying no contexto escolar (Bauer, Lozano & Rivara, 2007;Bowllan, 2011;Caballo et al, 2011;Cross et al, 2011;Fung, 2011;Jenson, Dieterich, Brisson, Bender, & Powell, 2010;Joronen et al, 2012;Kärnä et al, 2011a;Kärnä et al, 2011b;Kim, 2006;McWilliam, 2010;Perkins, Craig, & Perkins, 2011;Salmivalli, Kärnä, & Poskiparta, 2011;Waasdorp, Bradshaw, & Leaf, 2012;Williford et al, 2012). Seis estudos tiveram ainda como objetivo testar intervenções que buscavam desenvolver alguma habilidade específica para o manejo do bullying, como, por exemplo, habilidades sociais, comportamentos antibullying, artes marciais, entre outros (Bauer et al, 2007;Cross et al, 2011;Domino, 2013;Fung, 2011;Kärnä et al, 2011a;McWilliam, 2010), sendo que alguns deles (6) também pretendiam que a intervenção interferisse em aspectos da saúde mental na infância (Domino, 2013;Fung, 2011;Kärnä et al, 2011b;Joronen et al, 2012;Tsang et al, 2011).…”
Section: Resultsunclassified
“…Por outro lado, nove intervenções apresentaram o modelo teórico que embasou a intervenção, sendo contemplados o Modelo de Processamento de Informações Sociais (Fung, 2011), o Modelo de Desenvolvimento Social (Jenson et al, 2010), o Modelo do Desenvolvimento Positivo da Juventude (Domino, 2013;Hui et al, 2011;Tsang et al, 2011), o Modelo Sócio-Ecológico (Waasdorp et al, 2012), o Modelo Teórico do Bem-Estar Escolar (Joronen et al, 2012), o Modelo Tradicional das Artes Marciais (Twemlow et al, 2008) e a Jurisprudência Terapêutica (McWilliam, 2010). O Modelo do Desenvolvimento Positivo da Juventude foi o mais contemplado, sendo mencionado por três dos estudos analisados (Domino, 2013;Hui et al, 2011;.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Studies evaluating the efectiveness of the program have shown that children in the schools where the program was applied encountered less peer rejection and bullying compared to schools where the program was not applied [35], and that there was a decrease in problematic behavior, especially 65% decrease in physical and verbal aggression [34].…”
Section: Bully Prevention In Positive Behavioral Interventions and Sumentioning
confidence: 99%